Papillary Thyroid Carcinoma Arising in Thyroglossal Duct Cyst and Locally Infiltrated to Hyoid Bone: Issue of Individualized Management (Bangladesh Journal of Nuclear Medicine, 2023)
Thyroglossal duct cyst (TGDC) is the most common developmental anomaly of the thyroid gland, while TGDC carcinoma with local infiltration to the hyoid bone is extremely rare. The reported case of papillary thyroid carcinoma (PTC) was diagnosed in TGDC along with local infiltration to the hyoid bone and needed individualized management. A 70-year-old male patient presented with a history of PTC arising in TGDC and locally infiltrated to the hyoid bone followed by total thyroidectomy and radical sistrunk operations and was referred to  National Institute of Nuclear Medicine and Allied Sciences (NINMAS) for radioactive iodine therapy (RAIT). His post-operative ultrasound of the neck revealed an irregular shaped, fungating, grossly non-homogenous mixed echogenic mass lesion invading the hyoid bone, measuring about 25 X 28 mm. Radioactive iodine(131I) of 150 mCi was administered because the residual hyoid bone mass was inoperable and he was on thyroxine suppression therapy. The post-therapy 131I scan (RxWBS) showed two intense foci of radiotracer concentration (RTC) in the upper area (above the thyroid bed) and an intense focal RTC in the fundal region of the stomach. The activity in the stomach region was evaluated by ultrasound imaging, which revealed a soft tissue mass or thickening of the mid-region of the posterior wall of the stomach (3.3 cm X 1.6 cm). A CT scan of the chest was also performed to rule out metastasis, and it revealed multiple nodular lesions in both lung fields (most likely secondary) as well as tiny subcentric lymphnodes in the lower pre- and right paratracheal regions after nearly one month of RAIT when the patient was stable for examination. EBRT is still under consideration as adjuvant therapy. Tyrosine kinase inhibitors (TKI) may be considered in cases of refractoriness to radioiodine and disease progression.Bangladesh J. Nuclear Med. 26(1): 67-70, 2023